Circuito auxiliar para equilíbrio da tensão e redução da corrente do ponto central do barramento CC aplicado a uma UPS sem transformador - Jank, Henrique (2016)
This work proposes the use of an auxiliary circuit to perform the voltage balancing and reduce the low frequency currents of the DC Bus center point of a three-phase transformerless UPS. The Bus voltage unbalance may occur due to the connection of unbalanced loads and non-idealities of the circuit and may impair the quality of the UPS output voltage. The low frequency current components occur due to the connection of non-linear or unbalanced loads. With the occurrence of these currents, there is an increase in the DC Bus voltage ripple, making it necessary to use a DC Bus with significant capacitance values. Moreover, these currents should increase the losses in the capacitor and deteriorate its lifespan. Thus, it is proposed the use of an auxiliary circuit comprising a switching branch and an inductor, whose function is to reduce the harmonic content from the currents flowing through the central point of the capacitive divider, in addition to ensuring the balancing of the DC Bus voltages. It is carried out the design of a three-phase transformerless UPS and the proposed auxiliary circuit, besides the design of its control systems. Simulation and experimental results demonstrate the procedures developed over this work and validate the functionality of the proposed circuit with respect to its purpose.